Hubungan Luas Ventilasi Ruangan Rumah Dan Pengetahuan Keluarga Dengan Kejadian Tuberkolosis Paru Di Puskesmas Sambung Makmur Kabupaten Banjar Tahun 2016 - Eka Handayani; Ridha Hayati; Pipit Indriani (HB PRESS, 2017)
Pulmonary Tuberculosis is a disease closely related to a weak economy it is estimated that 95% of the cases of Pulmonary Tuberculosis occur in developing countries which is relatively poor. According to WHO in 1999, Indonesia is a contributor to the disease Pulmonary Tuberculosis is the third largest in the world as many as 583,000 cases after India as many as 2 million cases and China as many as 1.5 million cases The purpose of this research is to know the relation the wide of house ventilation And Family Knowledge With Pulmonary Tuberculosis incidence at Sambung Makmur Public Health Center of 2016. The purpose of this research is to know the relation of Area Ventilate Room And Family Knowledge With Lung Tuberculosis at Sambung Makmur Public Health Center in 2016. The population in this study were all patients with pulmonary tuberculosis in 2016 as many as 23 people and 23 people with pulmonary tuberculosis patients who have almost the same characteristics So the total population of the study was 46 people. Sampling by purposive sampling, done by Chi Square statistical test. There is a significant relationship between the wide of house ventilation and Pulmonary Tuberculosis incidence and the risk of pulmonary tuberculosis 3.1 times greater in homes with the vast circumstances of room ventilation did not meet the standards compared to homes where the vast majority of ventilation rooms meet the standards. There was no significant association between family knowledge and Pulmonary Tuberculosis incidence